Ascus apical apparatus and ascospore characters in Xylariaceae - Nuttika Suwannasai; Margaret A. Whalley; Anthony J.S. Whalley; Surang Thienhirun; Prakitsin Sihanonth (IMA Fungus)
Ascus apical apparatus and ascospore characters in Xylariaceae